Insufficient initial treatment but good recovery after diagnosis of pulmonary actinomycosis. Issue 12 (31st December 2019) - Ito, Toshiki; Yoshida, Takayuki; Sakuraba, Motoki; Tanaka, Akihiko; Hamada, Kunio; Ito, Akihide
Abstract: Actinomycosis is an infrequent invasive bacterial disease. Although multiple different clinical features of actinomycosis have been described, pulmonary actinomycosis (PA) is a rare but challenging diagnosis and complete cure to make. Here we report the case of a 41-year-old Asian woman who had a mass-like consolidation in the right middle lung field. The lung lesion was exacerbated after initial treatment. After diagnosis of PA, thoracoscopic resection combined with intravenous and oral penicillin made a good recovery.